An evidence‐based system for health surveillance of occupational divers. Issue 10 (October 2016) - Sames, C.; Gorman, D.; Mitchell, S.; Sandiford, P.
Abstract : Background: The value of the commonly required routine annual medical examination of occupational divers has been questioned, and there is a need for a robust, evidence‐based system of health surveillance for this group of workers. Aims: To determine whether the medical examination and investigation component of occupational divers' routine comprehensive health surveillance adds significantly to the information gained from the questionnaire component in determining fitness for diving. Methods: An occupational diver database was interrogated to identify divers issued with a 'limited' medical clearance or considered 'unfit' for diving over a 5‐year period. Reasons for the 'unfit' or 'limited' designation and the source of the critical information, whether the annual health questionnaire or the medical examination or questionnaire component (or both) of the initial or 5‐yearly comprehensive medical evaluation, was recorded. For divers completing the 5‐yearly repeat comprehensive medical evaluation, the sensitivity and specificity of the questionnaire alone for determining unfitness for diving was compared with that of a nominal 'gold standard'. Results: Of 5178 certificates issued to 2187 divers over a 5‐year period, 158 (3%) were provisionally designated as either 'limited' or 'unfit'. Of nine divers identified by the examination component of the 5‐yearly comprehensive medical evaluation, four were eventually designated 'fit', two 'limited', and three were lost to follow up. None who had completed subsequent investigations remained 'unfit'. The sensitivity and specificity of the questionnaire to detect unfit divers compared with the gold standard were 84.6 and 99.3%, respectively, and its accuracy was 98.9%. Conclusion: The current New Zealand occupational diver medical certification process, comprising annual health questionnaires and 5‐yearly full examinations, detects all health issues critical to the determination of fitness to dive.